JAKARTA GADGET TREND CENTER - Gio Timotius; Suryono Herlambang (Jurusan Arsitektur dan Perencanaan, 2019)
It is commonly known that in this present days technology has been heavily linked with daily life with various affects. These influences has made basic human needs also changed functionally. For example the existence of smartphone has become one of the most crucial thing on supporting daily life activities. Smartphones are only 1 of the various types of gadgets (devices) that have specific functions for users for the sake of facilitating their activities. The existence of gadgets slowly over time began to change into one of the primary needs of millennial society today. A concrete example that we can see is the ease of transportation, transactions, and interacting with the help of smartphone usage. Not only in terms of practical functions, gadget technology also has functions of entertainment & hobbies such as digital cameras, drones, game consoles, 3D printing, etc. Based on concrete statements and phenomena of human civilization now, the existence of the gadget trend center is considered important. And also based on a design method that discusses data and analysis of weaknesses and strength of site locations and approved programs, the Jakarta Gadget Trend Center is produced. This project is designed to have the maximum level of space efficiency and has a contextual response to the style and topography of the area in the form of mass, interior, and facade. AbstrakSudah diketahui secara umum bahwa di masa kini teknologi sudah melekat dengan kehidupan sehari - hari masyarakat umum dengan pengaruh yang beragam. Pengaruh tersebut membuat kebutuhan dasar manusia juga berubah secara fungsional. Contohnya keberadaan smartphone atau ponsel pintar menjadi benda paling krusial dalam mendukung kemudahan dan kelancaran beraktivitas sehari - hari. Smartphone hanya 1 dari sekian jenis gadget (gawai) yang memiliki fungsi tertentu bagi penggunanya untuk kepentingan yang memudahkan kegiatan mereka. Keberadaan gadget perlahan seiring berjalannya waktu mulai berubah menjadi salah satu kebutuhan primer masyarakat milenial kini. Contoh konkrit yang dapat kita lihat fenomenanya adalah kemudahan bertransportasi, bertransaksi, dan berinteraksi dengan penggunaan smartphone. Bukan hanya dari segi fungsi praktis, teknologi gadget juga memiliki fungsi entertainment & hobby seperti kamera digital, drone, game console, 3D printing, dsb. Berdasarkan pernyataan dan fenomena konkrit dari peradaban manusia kini, keberadaan pusat tren gawai dirasa penting. Dengan berbasis metode perancangan yang mengacu pada data dan analisis mengenai kelemahan dan kelebihan lokasi tapak maupun program yang disarankan, maka dihasilkanlah Jakarta Gadget Trend Center. Proyek ini didesain untuk memiliki tingkat efisiensi ruang semaksimal mungkin dan memiliki respons kontekstual terhadap langgam serta topografi kawasan dalam bentukan massa, interior, maupun fasad.